A qualitative comparison of system dynamics, discrete event simulation, and agent-based simulation - Sarmiento-Vásquez, Alfonso (2017)
Systems dynamics, discrete event simulation, and agent-based simulation are three widely used forms of modeling for business decision making. These paradigms are focused on representing the behavior of systems over time, although in different perspectives. This paper compares the three paradigms in 10 aspects and it can serve as an indicator to choose the most appropriate technique to a required problem.